Bilirubin Oxidase from Myrothecium Verrucaria Physically Absorbed on Graphite Electrodes. Insights into the Alternative Resting Form and the Sources of Activity Loss - Acuna-Castillo, C; Tasca-Gottardo, F; Tasca-Gottardo, F (Public Library of Science, 2015)
The oxygen reduction reaction is one of the most important chemical processes in energy converting systems and living organisms. Mediator-less, direct electro-catalytic reduction of oxygen to water was achieved on spectrographite electrodes modified by physical adsorption of bilirubin oxidases from Myrothecium verrucaria. The existence of an alternative resting form of the enzyme is validated. The effect on the catalytic cycle of temperature, pH and the presence of halogens in the buffer was investigated. Previous results on the electrochemistry of bilirubin oxidase and on the impact of the presence of halogens are reviewed and reinterpreted. © 2015 Tasca et al.